2000
DOI: 10.1046/j.1365-2141.2000.02426.x
|View full text |Cite
|
Sign up to set email alerts
|

An Asian variant of intravascular large B-cell lymphoma: clinical, pathological and cytogenetic approaches to diffuse large B-cell lymphoma associated with haemophagocytic syndrome

Abstract: Diffuse large B-cell lymphoma with haemophagocytic syndrome (BCL-HS) has been reported mainly in Asia and is regarded as a distinct variant of intravascular lymphoma (IVL). However, it is unclear whether all cases of BCL-HS fall within the framework of IVL and available clinical information is limited. We analysed 25 cases with BCL-HS, including 11 autopsied cases (median, 66 years; male-female ratio, 1.1:1). The patients presented with fever, anaemia, thrombocytopenia, hepatosplenomegaly, haemophagocytosis, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
142
2
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(156 citation statements)
references
References 27 publications
10
142
2
2
Order By: Relevance
“…Chromosomeanalysis of the bone marrow cells in the present case showed extremely complex abnormalities mixed with a normal karyotype (Fig 6). The hypotetraploidy might suggest gains involving chromosome 18, which has been reported as a candidate for common chromosome abnormalities in the AIVL (14). In addition, 8p21 and 19ql3, both of which Shimazaki et al reported as characteristic chromosome abnormalities in their cases of DLBLwith HPS, are also involved in the present case (18).…”
Section: Case Reportmentioning
confidence: 57%
See 2 more Smart Citations
“…Chromosomeanalysis of the bone marrow cells in the present case showed extremely complex abnormalities mixed with a normal karyotype (Fig 6). The hypotetraploidy might suggest gains involving chromosome 18, which has been reported as a candidate for common chromosome abnormalities in the AIVL (14). In addition, 8p21 and 19ql3, both of which Shimazaki et al reported as characteristic chromosome abnormalities in their cases of DLBLwith HPS, are also involved in the present case (18).…”
Section: Case Reportmentioning
confidence: 57%
“…The pathologic diagnosis of IVL was based on the intravascular and sinusoidal involvement of neoplastic large B-cells in the liver wedge biopsy, making the diagnosis of AIVLstrongly indicated from the clinical viewpoint. Wehave recently proposed diagnostic criteria for AIVL for the purpose of early diagnosis and prospective studies of this disease (Table 1) (14). The present case, on the second admission, did not match for "criterion I.e.…”
Section: Case Reportmentioning
confidence: 72%
See 1 more Smart Citation
“…[12][13][14] These include a purportedly distinct variant of intrasinusoidal splenic LBCL occurring primarily in Asians which is associated with histocytic proliferation, prominent hemophagocytosis, and aggressive behavior. [15][16][17] The nature of these latter cases remains unclear and it has been speculated that some may represent a variant of intravascular LBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Prognosis is uniformly poor with better outcomes observed with the ''cutaneous variant,'' which is associated with skin lesions in the absence of systemic involvement [6][7][8][9]. An ''Asian variant'' of the disease mostly reported in the Japanese literature differs from the presentation of IVL in the Western literature as it is associated with a hemophagocytic syndrome, bone marrow involvement, hepatosplenomegaly, and thrombocytopenia, while cutaneous and CNS lesions are uncommon [15,16]. IVL is considered a disseminated disease and treatment with combination chemotherapy including anthracyclines is recommended along with inclusion of methotrexate or cytarabine when there is CNS involvement [7].…”
Section: Commentarymentioning
confidence: 99%